Determining the Role of Inefficiency on Elasticity of Output Supply and Input Demand: A Case Study of Irrigated Wheat in 27 provinces of Iran - Garshasbi, Alireza; Khosropour, Hossein; Rahimian, Narges; Behrooz, Aref; Sedighi, Somaye (Asian Journal of Agriculture and Rural Development, 2014)
This article appraises the impressions of technical and price or allocative inefficiency on elasticity of the supply of wheat and demand of its inputs in 27 provinces of Iran. To this purpose, first the technical, price and economic efficiency has been calculated utilizing the stochastic frontier functions of production and cost. The influencing factors of efficiency including: the degree of scale economies, the share of technology in manufacturing process, the share of governmental supports, the cost of production processes and the experience have been estimated via a panel data approach. At the end, rejecting the hypothesis of perfect efficiency of farmers in production, the functions of output supply and input demand have been assessed in two scenarios (concerning efficiency and inefficiency) using a profit function and the impact of general (economic) inefficiency on relative and crossover elasticities of output and input are evaluated. The results show that the average of technical, price and economic efficiency of irrigated wheat respectively equal to 69, 63 and 45 percent. The estimated parameters have been affected, concerning the inefficiency. Although relative elasticities of output and inputs are appeared with expected signs, entering the inefficiency, elasticity of irrigated wheat is generally increased.